Effects of polymers on complexation efficiency of aceclofenac-beta cyclodextrin inclusion complex - MOHAMMED TAHIR ANSARI,; POONAM RISHESHWAR,; SADATH ALI, (International Journal of Pharma and Bio Sciences, 2017)
Aceclofenac (ACF) is a poorly water soluble analgesic drug. An effort has been made to enhance the solubility through forming inclusion complex with an aim to improve the complexation efficiency of β-Cyclodextrin (βCD). The inclusion complex was formed by kneading method. Hydrophilic polymers such as Poly Vinyl Pyrolidone (PVP), Sodium Carboxy Methyl Cellulose (SCMC), Hydroxy Propyl Methyl Cellulose (HPMC) and hydrophobic polymer such as Ethyl Cellulose (EC) were used to enhance the solubility as well as the CE of ACF- βCD inclusion complex. Phase solubility studies were carried out to evaluate the solubilizing power of β-cyclodextrin (βCD) along with the optimized concentration of polymers. Complexation efficiency and stability constant was calculated from the phase solubility studies. Higher values of solubility constant for ternary complexes clearly proves the beneficial effects of added polymers. CE was enhanced maximum by EC but the dissolution rate followed the following sequence PVP>HPMC>SCMC>EC. Selected ternary mixtures of ACF-βCD inclusion complex were subjected to characterization by Differential Scanning calorimetry (DSC), Fourier Transform InfraRed Spectroscopy (FTIR) and Scanning Electron Microscope (SEM) techniques. The results suggested the formation of inclusion complex with limited or no chemical interaction.